2005
DOI: 10.1002/hyp.5961
|View full text |Cite
|
Sign up to set email alerts
|

Response of surface water chemistry to reduced levels of acid precipitation: comparison of trends in two regions of New York, USA

Abstract: Abstract:In light of recent reductions in sulphur (S) and nitrogen (N) emissions mandated by Title IV of the Clean Air Act Amendments of 1990, temporal trends and trend coherence in precipitation (1984-2001 and 1992-2001) and surface water chemistry (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001) were determined in two of the most acid-sensitive regions of North America, i.e. concentrations at all sites, and decreasing trends in NO 3 , C B , and H C concentrations and increasing trends in dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 60 publications
4
79
1
Order By: Relevance
“…To our knowledge, this procedure has only been used by Burns et al [55], after hyperbolic or log regression fit of the data. Other authors mention the use of the partial MK test with discharge or other parameters as covariates [24,40].…”
Section: Trend Detection and Quantificationmentioning
confidence: 99%
“…To our knowledge, this procedure has only been used by Burns et al [55], after hyperbolic or log regression fit of the data. Other authors mention the use of the partial MK test with discharge or other parameters as covariates [24,40].…”
Section: Trend Detection and Quantificationmentioning
confidence: 99%
“…Directional trees corresponding to drainage network structure (i.e., channel width) have been used to modify the geostatistical framework (Monestiez et al, 2005;Bailly et al, 2006). Chokmani and Ouarda (2004) used a physiographical space-based kriging method incorporating physiographical and meteorological characteristics of stream gauging stations with multivariate analysis techniques to modify in-stream distance. Still, applying geostatistical techniques to stream networks is a relatively new field of research and the limited findings to date do not clearly indicate which distance measure to use .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, reported long-term trends in nitrate are positive, neutral and negative although decreases in nitrate appear to be more frequent than increases. Declines in nitrate and lack of trends in nitrate have been observed in stream water and lakes in New York state in USA during the 1980-2000 (Burns et al, 2006), declines were found in reservoirs and stream waters the Erzgebirge in southeast Germany in 1993(Ulrich et al, 2006, in stream waters in forest catchments in the Czech Republic Figure 4 Monthly means of observed and predicted nitrate concentrations in four catchments. Predictions based on models presented in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…In the Italian Alps, significant increases in stream water nitrate were found in old-growth forests catchments in relatively high N deposition areas ). The factors used to explain the observed trends in the studies mentioned above include enhanced growth of forests that were previously negatively impacted by acid deposition (Ulrich et al, 2006;Vesely et al, 2002), trends in N deposition and decreased soil capacity to retain deposited N (Kopacek et al, 2005;Burns et al, 2006;Rogora et al, 2001). Forests at the sites in our study have not shown signs of growth deterrence by acid deposition and are presently not growing faster than previously (Solberg et al, 2004) while N deposition in the sites has not changed significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation